EVALUASI KEKAYAAN HIGH NET WORTH INDIVIDUAL UNTUK PERENCANAAN MASA DEPAN (STUDI KASUS) - , Erika Amelia, Sukmawati Sukamulja, Prof., Dr., M.M. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
There is a new awareness to the financial things, which is not only apply to companies but also for individuals within the family especially the High Net Worth Individual (HNWI), individuals or families with a net worth of at least U.S. $ 1 million. This is a potential opportunity for financial consulting services to HNWI and the development of the current global financial industry. The failure of the managing wealth will result that asset become diminished or exhausted due to continuous use and / or eroded by inflation flow. Wealth should be managed by doing protection with diversification of assets and purchasing of insurance. In the other point, wealth must be accumulated by investing so the value remains the same or increased, in order to plan for the future and to ensure / maintain client's lifestyle. Investments should consider the level of liquidity of assets and client risk tolerance being strongly associated with risk and return factors. As growing old, client should be noted to the distribution of assets. The importance of managing HNWI / families fortune create a new specialization in the financial management called wealth management. Related professions in the field of wealth management is wealth managers.